Improving "Adequacy" Concepts in Education Finance: A Heuristic Examination of the Professional Judgment Research Protocol - R. Craig Wood; R. Anthony Rolle (Educational Considerations, 2007)
State legislatures, policy analysts, and researchers are attempting, in many instances, to measure levels of equity as well as the levels of adequacy provided by public elementary and secondary education funding mechanisms.
Keywords: adequacy; opportunities; Professional Judgment Model; education; research; concepts; methodologies